2014
DOI: 10.1177/1063426614543950
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Organized Activities and Conduct Problems in Elementary School

Abstract: The goal of this study was to test a mediation model in which social skills mediate the relationship between participation in organized activities and conduct problems among elementary school children. Two moderators of these associations were also examined, namely, gender and reception of special education services. A total of 563 children (45% girls; Mage = 8.44) were surveyed. The findings revealed that, after controlling for important covariates, more frequent activity participation predicted better social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
5
14
0
Order By: Relevance
“…In line with the results of other recent studies [ 17 , 18 , 54 , 55 ], we found no longitudinal association between characteristics of sports participation and externalizing problems. This might be explained with the help of the intermediate concept of ‘effortful control’.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the results of other recent studies [ 17 , 18 , 54 , 55 ], we found no longitudinal association between characteristics of sports participation and externalizing problems. This might be explained with the help of the intermediate concept of ‘effortful control’.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that membership in a sports club and frequency of sports participation were longitudinally associated with better prosocial behaviour confirms what has been described in other studies [ 18 , 54 , 58 ]. The disciplinary effect of engagement in sports activities on the behaviour of children [ 18 , 41 ] probably also applies more specifically to their prosocial behaviour [ 59 , 60 ]. The repetition of rules, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of special education status, we selected these variables, because they have been used successfully as matching variables in two studies which examined the association between participation in out of school activities and youth development (O'Connor & Jose, 2012;Zarrett et al, 2009). We decided to include special education status as an additional matching variable because previous research has shown that students receiving special education services were associated with lower levels of engagement in organized activities (Denault & Déry, 2015) and lower academic achievement (Bussing et al, 2012) than their peers not receiving special education services.…”
Section: Discussionmentioning
confidence: 99%
“…The development of social skills is a part of the socialization process in individuals, and the training should be exclusively offered on the basis of this process (32). Training of emotional, social skills bring several benefits for individuals, including regulated emotions, stress control, emotional management, self-control, and interaction and subsequently lead to a decrease in non-social and aggressive behaviors and an improvement in interactions and desirable behaviors due to the person-environment interactions (33).…”
Section: Discussionmentioning
confidence: 99%